2023
DOI: 10.3389/fendo.2023.1150171
|View full text |Cite
|
Sign up to set email alerts
|

The Na+/K+-ATPase: A potential therapeutic target in cardiometabolic diseases

Abstract: Cardiometabolic diseases (CMD) are a direct consequence of modern living and contribute to the development of multisystem diseases such as cardiovascular diseases and diabetes mellitus (DM). CMD has reached epidemic proportions worldwide. A sodium pump (Na+/K+-ATPase) is found in most eukaryotic cells’ membrane and controls many essential cellular functions directly or indirectly. This ion transporter and its isoforms are important in the pathogenesis of some pathological processes, including CMD. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 165 publications
0
3
0
Order By: Relevance
“…Our findings revealed significant downregulation of ATPase Na + /K + transporting subunit alpha 1 (ATP1A1), a major component of Na + / K + pump that has a recognisable role in maintaining the electrochemical gradient that arises from the difference in electrical potential and ion concentration across the cell membrane (Obradovic et al, 2023). Hence, dysregulation in ATP1A1 associated with ROSI exposure could have a dramatic effect on the contractile machinery, which could potentially result in elevating cytosolic calcium levels, leading to sustained muscle contraction and, eventually, muscle weakness.…”
Section: Molecular Insights Into Tzd-induced Ac16 Cellular Deathmentioning
confidence: 86%
“…Our findings revealed significant downregulation of ATPase Na + /K + transporting subunit alpha 1 (ATP1A1), a major component of Na + / K + pump that has a recognisable role in maintaining the electrochemical gradient that arises from the difference in electrical potential and ion concentration across the cell membrane (Obradovic et al, 2023). Hence, dysregulation in ATP1A1 associated with ROSI exposure could have a dramatic effect on the contractile machinery, which could potentially result in elevating cytosolic calcium levels, leading to sustained muscle contraction and, eventually, muscle weakness.…”
Section: Molecular Insights Into Tzd-induced Ac16 Cellular Deathmentioning
confidence: 86%
“…In the biopsies of patients with heart failure, for instance, the Na + , K + -ATPase activity was much lower. The aldosterone antagonist was still another factor in the regulation of Na + , K + -ATPase after a heart attack since it lowered hyperaldosteronism and decreased Na + , K + -ATPase activity ( Obradovic et al, 2023 ). In this study, it was found that ISO-exposed animals had decreased cardiac Na + , K + -ATPase activity, which may be related to increased lipid peroxidation and membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…Na + -K + -ATPase enzyme and Ca 2+ -ATPase enzyme, ubiquitous enzymes in the heart, play a crucial role in process of CVDs ( Fedosova et al, 2021 ). Na + -K + -ATPase transports two Na + ions extrude out of the cell in exchange for one K + ions, thereby maintaining the concentration gradients across the cell membrane ( Fedosova et al, 2021 ; Obradovic et al, 2023 ). Ca 2+ -ATPase, a crucial role for cellular Ca 2+ homeostasis, maintains normal intracellular calcium concentration and prevents calcium overload ( Nguyen et al, 2023 ; Ye et al, 2023 ).…”
Section: Pharmacological Activities Of Sfi On Cvdsmentioning
confidence: 99%